PENGARUH DIMENSI PROPENSITY OF TRUST, PERCEIVED RISK, PERCEIVED USEFULNESS, PERCEIVED EASE TO USE TERHADAP INTENTION TO TRANSACT PADA BUSINESS TO CUSTOMER TOKO ONLINE - INDAHWATI, FENNY (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
This study aims to determine the effect of the legal framework of trust, integrity retailer trust, technology trust on perceived risk and the influence of perceived risk, perceived usefulness and perceived ease to use against the intention to Transact the Business-To-Consumer Electronic Commerce online stores. The research was also to determine the ability of the mediating influence of perceived risk legal framework of trust, integrity retailer trust, technology trust on intention to Transact. Research design of this study is causal, this study used five independent variables (latent exogenous) variables between the (mediating), and the dependent variable (endogenous latent). The sampling technique was purposive sampling studies, and determined the number of samples of 148 samples. Data analysis techniques using a structural equation model. The findings of this study indicate that the legal framework of trust, integrity retailer trust, technology trust shown to affect the perceived risk. Perceived risk and perceived usefulness affect the intention to Transact the Business-To-Consumer Electronic Commerce online stores. Perceived risk legal framework capable of mediating the effect of trust, integrity retailer trust, technology trust on intention to Transact.